Peran Beban Kerja dan Motivasi Kerja dalam Mepengaruhi Kinerja Melalui Kepuasan Kerja - Indra Thalib; Rina Anindita; Dian Alfia Purwandari (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
This study aims to analyze the performance of nurses which is influenced by workload and motivation through job satisfaction. This research was conducted on nurses at Primaya Hospital, Bekasi Utara, where 152 nurses were used as respondents. The data collection technique was carried out using a questionnaire with measurement of the likert scale and interval scale. The analytical method used is Partial Least Square (PLS) using software WarpPLS 7.0. The results of this study indicate that motivation has a positive and significant effect on nurse performance. Meanwhile workload has no effect on performance. Satisfaction has no effect on performance. This result is expected to be taken into consideration for related parties in maintaining nurse performance